Safety profile comparison of chimeric live attenuated and Vero cell-derived inactivated Japanese encephalitis vaccines through an active surveillance system in Australia. Issue 1 (31st December 2022) - Islam, Nazmul; Lau, Colleen; Leeb, Alan; Mills, Deborah; Furuya-Kanamori, Luis
ABSTRACT: Limited information is available about post-marketing safety of Japanese encephalitis (JE) vaccines. Using data from SmartVax, an active surveillance system for monitoring vaccine safety, adverse events following immunizations (AEFIs) were compared between the two JE vaccines available in Australia (a chimeric live attenuated vaccine [Imojev] and a Vero cell-derived inactivated vaccine [JEspect]). Data from 2756 patients (1855 Imojev and 901 JEspect) were included. Overall (7.0%), systemic (2.8%), and local (1.9%) AEFIs were uncommon. There were no significant differences in the odds of overall (OR = 1.27; 95%CI: 0.91–1.77), systemic (OR = 1.23; 95%CI: 0.74–2.06), or local (OR = 1.20; 95%CI: 0.65–2.22) AEFIs with Imojev compared to JEspect. There was an increase in odds of overall AEFI in patients aged <5 years (OR = 2.39; 95%CI: 1.10–5.19) compared to those aged >50 years. Both JE vaccines available in Australia are safe and well tolerated. Odds of AEFIs were age-dependent, young children should be carefully observed for AEFIs after vaccination.